Information and consent for newborn screening: practices and attitudes of service providers. Issue 9 (29th August 2008) - Kerruish, N J; Webster, D; Dickson, N
Abstract : Objectives: To gather information about the practices and attitudes of providers of maternity care with respect to informed consent for newborn screening (NBS). Methods: A questionnaire concerning information provision and parental consent for NBS was sent to all 1036 registered lead maternity carers (LMC) in New Zealand. Results: 93% of LMC in New Zealand report giving parents information concerning NBS, most frequently after delivery (73%) and in the third trimester (60%). The majority (85%) of LMC currently obtain some form of consent (verbal or written) for NBS from parents and consider this to be the ideal approach (94%). Despite this a significant minority of LMC (23%) reported considering that NBS should be mandatory. Of those in our survey who believed that NBS should be mandatory, paradoxically most (89%) still believed that some form of parental consent should be obtained; of those who believed testing should not be mandatory, only a small proportion (10%) would accept parental refusal without question. Conclusions: When the results of this survey are considered in conjunction with existing evidence there appears to be a consensus that good quality information in the prenatal period should be an integral part of any NBS programme. The issue of consent is more complex and there is less agreement on the preferred degree of parental involvement in decisions to allow babies to undergo NBS. A policy that both strongly recommends NBS but also allows parental choice appears to be most consistent with the views of LMC in this survey.